Inhibition of CFTR‐mediated intestinal chloride secretion as potential therapy for bile acid diarrhea. Issue 10 (3rd July 2019) - Duan, Tianying; Cil, Onur; Tse, C. Ming; Sarker, Rafiquel; Lin, Ruxian; Donowitz, Mark; Verkman, Alan S.
ABSTRACT: Bile acid diarrhea (BAD) is common with ileal resection, Crohn's disease, and diarrhea‐predominant irritable bowel syndrome. Here, we demonstrate the efficacy of cystic fibrosis transmembrane conductance regulator (CFTR) inhibitor ( R )‐benzopyrimido‐pyrrolo‐oxazine‐dione‐27 (BPO‐27) in reducing bile acid‐induced fluid and electrolyte secretion in colon. Short‐circuit current measurements in human T84 colonic epithelial cells and planar colonic enteroid cultures showed a robust secretory response following mucosal but not serosal addition of chenodeoxycholic acid (CDCA) or its taurine conjugate, which was fully blocked by CFTR inhibitors, including ( R )‐BPO‐27. ( R )‐BPO‐27 also fully blocked CDCA‐induced secretory current in murine colon. CFTR activation by CDCA primarily involved Ca 2+ signaling. In closed colonic loops in vivo, luminal CDCA produced a robust secretory response, which was reduced by 70% by ( R )‐BPO‐27 or in CFTR‐deficient mice. In a rat model of BAD produced by intracolonic infusion of CDCA, ( R )‐BPO‐27 reduced the elevation in stool water content by >55%. These results implicate CFTR activation in the colon as a major prosecretory mechanism of CDCA, a bile acid implicated in BAD, and support the potential therapeutic efficacy of CFTR inhibition in bile acid‐associated diarrheas.—Duan, T., Cil, O., Tse, C. M., Sarker, R., Lin, R., Donowitz, M., Verkman, A. S. Inhibition of CFTR‐mediated intestinal chloride secretion as potential therapy for bile acid diarrhea. FASEB J. 33, 10924–10934 (2019). www.fasebj.org